Endurance Athletes Are More Resistant to Mental Fatigue Than Nonathletes - Daneshgar-Pironneau, Sarvenaz; Audiffren, Michel; Lorcery, Alison; Benraïss, Abdelrahni; Mirabelli, Francesco; Gargioli, Davide; André, Nathalie (Research quarterly for exercise and sport, 2025)
Acute mental fatigue refers to a temporary decline in cognitive function resulting from prolonged mental effort pertaining to a cognitively demanding task. Previous studies have indicated that acute mental fatigue decreases performance on subsequent physical effortful tasks as well as the capacity and/or motivation to invest mental effort. Scholars have recently suggested that aerobic training can enhance willpower. We hypothesized that endurance athletes are less responsive to the detrimental effects of acute mental fatigue than are nonathletes. Two groups of participants (50 athletes vs. 50 nonathletes) completed a sequential task protocol involving 30 minutes of a modified computerized incongruent Stroop task (effortful task) and 30 minutes of watching a documentary (control task), which were counterbalanced between two separate sessions; these tasks were followed by a time-to-exhaustion (TTE) handgrip task at 13% of participants' maximal voluntary contraction (dependent task). Psychophysiological indices (preejection period, heart rate variability, and respiratory rate) were assessed continuously throughout the experiment. The behavioral results indicated that only nonathletes exhibited worse performance on the TTE handgrip task after performing the Stroop task. The performance of participants in both groups was similarly impacted by mental fatigue during the Stroop task, and all the participants reported higher levels of subjective fatigue after completing the Stroop task. The psychophysiological data suggest that sympathetic activity decreased over time during these two cognitive tasks due to habituation (i.e. decreased arousal). Overall, these results suggest that endurance athletes are less susceptible to the negative effects of acute mental fatigue.